Іn Search of Soviet Fashion: Business Trips to the «Trendsetting» Countries in 1950–1960s - Корнієнко, Ольга (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2016)
The article deals with business trips of Soviet designers and specialists in the field of light industry to the developedcapitalist countries such as France, the USA and Italy. In the studied period the design concept of the Soviet fashion is formed and the fashion shows are held at the international level, therefore it is important for the USSR to choose the right benchmark in the fashion industry. Basing on the analysis of Soviet specialists reports, the author comes to conclusion that the conceptual differences between “socialistic” and “capitalistic” fashion belonging to the official discourse were not significant in the actual practice of the Soviet designers.